Factors Affecting Tri Hita Karana Harmony in Traditional Balinese Settlements - Wijaya, Komang Arya Partha; Wiranegara, Hanny Wahidin; Supriatna, Yayat (Universitas Diponegoro Publishing Group, Indonesia, 2024)
Tri Hita Karana's philosophy of Balinese people is reflected in harmony with God (parahyangan), with others (pawongan), and with the environment (palemahan). In realizing these values of harmony, Balinese people have customs and culture in arranging their traditional settlement. Factors in traditional settlements that are assumed to influence the harmony are temple, banjar, and zoning. This study aims to examine those factors. Design study is questionnaire survey methode. The hypothesis was tested using multiple linear regression techniques in 200 respondents between the ages of 18-68. The results showed that the temple, banjar, and zoning had significant effect on the harmony of Balinese people. Partially, temple and banjar had a significant effect, while zoning did not show a significant effect. Community patterns and customary systems become more dominant than zoning. Furthermore, the availability of land become a constraint, so that the holy places, banjar, and setra in the zoning follow customary agreements and regulations. Based on these findings, the preservation of these three elements in traditional Balinese settlement needs to be maintained as part of local culture and wisdom to keep the harmony in the traditional Balinese community.